Botanophila–Epichloe Interaction in a Wild Grass, Puccinellia distans, Lacks Dependence on the Fly Vector - Górzyńska, Karolina; Lembicz, Marlena; Olszanowski, Ziemowit; Leuchtmann, Adrian (My University, 2011)
In grass-infecting Epichloe (Ascomycetes: Clavicipitaceae) fungi, the transfer of spermatia for fungal fertilization depends on an insect vector: flies of the genus Botanophila (Diptera: Anthomyiidae). The flies use the fungal stroma, a spore-producing fungal structure surrounding the grass inßorescence, for laying eggs and as a food source for both adults and larvae. This fly-fungus interaction is generally regarded as obligatory and mutualistic. Two Botanophila taxa were noted among four populations of the nonagricultural grass Puccinellia distans (L.) Parl. that were infected with the fungus Epichloe typhina (Pers.) Tul. However, during the 7 yr of field observations, Botanophila flies were present every year in only one population of P. distans. The number of eggs per stroma ranged from zero to four and differed with year and site. Overall, eggs (or larvae) were observed on only 132 (19.2%) of the 687 stromata examined during the survey, with one (13.8%), two (4.5%), or more than two (0.9%) per stroma. However, 90.8% of the examined stromata were fertilized and produced perithecia, suggesting that other mechanisms or vectors of spermatia were responsible for fertilization.
Keywords: Anthomyiidae; Botanophila sp.; Epichloe sp.; fly-fungus interaction; Puccinellia distans